2006
DOI: 10.1021/nl061160x
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Carbon Nanotubes Are Non-Cytotoxic and Preserve the Functionality of Primary Immune Cells

Abstract: Carbon nanotubes are emerging as innovative tools in nanobiotechnology. However, their toxic effects on environment and health have become an issue of strong concern. In the present study, we address the impact of functionalized carbon nanotubes (f-CNTs) on cells of the immune system. We have prepared two types of f-CNTs, following the 1,3-dipolar cycloaddition reaction (f-CNTs 1 and 2) and the oxidation/amidation treatment (f-CNTs 3 and 4), respectively. We have found that both types of f-CNTs are uptaken by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
314
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(332 citation statements)
references
References 47 publications
12
314
2
4
Order By: Relevance
“…Apart from helping better solubility, nanotube dendrimer composite can be used for DNA and siRNA delivery with better efficiency. Pristine nanotube has also been shown to be toxic compared to chemically functionalized CNTs [47][48][49][50][51] . There are speculation that dendrimer wrapped nanotube can be better suited for the delivery of nucleic acid with less toxicity 41,52 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from helping better solubility, nanotube dendrimer composite can be used for DNA and siRNA delivery with better efficiency. Pristine nanotube has also been shown to be toxic compared to chemically functionalized CNTs [47][48][49][50][51] . There are speculation that dendrimer wrapped nanotube can be better suited for the delivery of nucleic acid with less toxicity 41,52 .…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the results obtained with the two compounds showed that the SKBR3 cells had a delayed response to MWCNT-quin so that their viability only began to decline at 5 µg/mL (P < 0.001). The results of the modified-MWCNTs toxicity at various concentrations could be related to various parameters, such as structure, length, purity, surface chemistry, agglomeration of CNTs in the culture medium, and surface functionalization [35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…The lowered toxicity may be due to a decreased tendency of the hydrophilic materials to associate with cell membranes or to decreased redox activity as a result of hydroxylation. Dumortier et al [31] show the nanotube toxicity is also sensitive to surface functionalization, and the degree of water solubility in particular. Functionalizing nanotubes by an oxidation/amidation treatment to introduce negatively charged surface groups produces water soluble CNTs that do not exert toxic effects on immune cells, B and T lymphocytes [31].…”
Section: The Role Of Carbon Surface Chemistrymentioning
confidence: 99%
“…Dumortier et al [31] show the nanotube toxicity is also sensitive to surface functionalization, and the degree of water solubility in particular. Functionalizing nanotubes by an oxidation/amidation treatment to introduce negatively charged surface groups produces water soluble CNTs that do not exert toxic effects on immune cells, B and T lymphocytes [31]. In contrast, the less-soluble formulation provokes secretion of proinflammatory cytokines from macrophages [31].…”
Section: The Role Of Carbon Surface Chemistrymentioning
confidence: 99%